Karakterizacija surovin za žganje cementnega klinkerja - Umek, Urban (Kovine zlitine tehnologije, 1997)
Cement clinker is smade from raw material with suitable chemical and mineralogical composition. Marl, with addition of limestone as the source of lime; quartz, flysch rock or other raw material rich with silicates as the source of silica; bauxite as the source of alumina and pyrite roastes as the source of iron oxide are the most common used raw mateials. Raw material may contain minerals which introduce sulphur into the raw mixture, as pyrite. Sulphur may cause the emission of ?$SO_3$? into the environment. The equivalent amount of alkali oxides in the raw mixture avoids the emission of ?$SO_3$?. Alkali oxides with ?$SO_3$? form alkali sulphates. Solid alkali sulphates leave the kiln together with clinker. With chemical analysis , 1.21-2.47 mass.% of ?$SO_3$? was determined in particular components of raw mixture. Investigation of the raw components with the x-ray diffraction could not incontestabily prove the presence of pyrite, because the pyrite amount was under the detection limit. STA measurements of the investigated samples demonstrated an exothermic reaction characteristics for the oxidation of pyrite at the temperatures from 440°C to 455°C and the corresponding weight loss as well. According to the weight loss the amount of ?$SO_2$? was calculated and subsequently the amount of pyrite. The investigated raw components contain from 0.5 d0 1.4 mass.% of pyrite.
Keywords: mineralne surovine; cementni klinkerji; kovinski oksidi; diferenčna termična analiza; rentgenska difrakcija; kemijska analiza